Pengaruh Pemberian Ekstrak Kulit Manggis pada Tikus Tuberkulosis yang Diberi Isoniazid terhadap Kadar Kolesterol - Millenia Hardyalensi; Indah Widyaningsih (Syntax Literate, 2023)
Patients with tubeculosis experience a decrease in the amount of cholesterol in the body due to an inflammatory process due to increased free radical formation due to oxidative stress arising as a result of increased phagocytic activity of monocytes and macrophages. Therefore, additional treatment is needed to overcome free radicals and ROS so that inflammation in TB patients does not get worse and cholesterol levels can return to normal. Treatment of isoniazid in TB patients can increase cholesterol levels but does not occur significantly, and the results are still lower than cholesterol levels in healthy individuals. Mangosteen peel extract has a variety of ingredients and one of them is xanthones which can be anti-inflammatory and can inhibit the increase in the formation of free radicals in TB patients. The main objective of this study was to determine the effect of mangosteen peel extract on TB rats given isoniazid on cholesterol levels. This research is a laboratory experimental study with a randomized posttest only method. The research sample used by the previous researcher, Dr. dr. Indah Widyaningsih., M. Kes was the blood serum of white rats (Rattus Norvegicus) aged 2-3 months with a body weight of 200-250 grams. The analytical test used in this study is the Kruskall-Wallis test. The results of the analysis that has been done by researchers, it is known that there is no effect of Mangosteen Skin Extract on Cholesterol Levels in TB rats given Isoniazid